(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2012)
Studying genetic variability for abiotic stresses like salt is important for crop improvement. To identify the genotypic diversity of wheat for salt tolerance, this study was carried out at Regional Agricultural Research Station, Bangladesh Agricultural Research Institute, Rahmatpur, Barisal in 2007-2008 using 12 genotypes under five different salinity levels (e.g. 4, 8, 12, 16 dS/m) and control. Plant morphological and yield contributing traits showed a range of variability. Genotypic variabilities were more prominent in plant height, number of spikes plant-1, number of grains plant-1, 100-grain weight and grain yield plant-1. Genotype G40 ranked top for most of the yield related traits followed by G33. While, G24 outperformed over all the genotypes for 100-grain weight and grain yield per plant. There was no effect of heading on salinity though other plant characters were affected by increasing level of salinity. Considering the responses of plant characters to salinity G40, G33 and G24 were found to be more salt tolerant than others. These three genotypes can therefore be useful for further genetic and physiological study. DOI: http://dx.doi.org/10.3329/bjpbg.v25i2.18661